Expansion and diversification of the MSDIN family of cyclic peptide genes in the poisonous agarics Amanita phalloides and A. bisporigera. (December 2016) - Pulman, Jane; Childs, Kevin; Sgambelluri, R.; Walton, Jonathan
Abstract Background The cyclic peptide toxins ofAmanita mushrooms, such as α-amanitin and phalloidin, are encoded by the "MSDIN" gene family and ribosomally biosynthesized. Based on partial genome sequence and PCR analysis, some members of the MSDIN family were previously identified inAmanita bisporigera, and several other members are known from other species ofAmanita . However, the complete complement in any one species, and hence the genetic capacity for these fungi to make cyclic peptides, remains unknown. Results Draft genome sequences of two cyclic peptide-producing mushrooms, the "Death Cap"A. phalloides and the "Destroying Angel"A. bisporigera, were obtained. Each species has 30 MSDIN genes, most of which are predicted to encode unknown cyclic peptides. Some MSDIN genes were duplicated in one or the other species, but only three were common to both species. A gene encoding cycloamanide B, a previously described nontoxic cyclic heptapeptide, was also present inA. phalloides, but genes for antamanide and cycloamanides A, C, and D were not. InA. bisporigera, RNA expression was observed for 20 of the MSDIN family members. Based on their predicted sequences, novel cyclic peptides were searched for by LC/MS/MS in extracts ofA. phalloides . The presence of two cyclic peptides, named cycloamanides E and F with structures cyclo(SFFFPVP) and cyclo(IVGILGLP), was thereby demonstrated. Of the MSDIN genes reported earlier from another specimen ofA. bisporigera, 9 of 14 were not found in the current genome assembly. Differences between previous and current results for the complement of MSDIN genes and cyclic peptides in the two fungi probably represents natural variation among geographically dispersed isolates ofA. phalloides and among the members of the poorly definedA. bisporigera species complex. BothA. phalloides andA. bisporigera contain two prolyl oligopeptidase genes, one of which (POPB) is probably dedicated to cyclic peptide biosynthesis as it is inGalerina marginata . Conclusion The MSDIN gene family has expanded and diverged rapidly inAmanita sectionPhalloideae . Together, A. bisporigera andA. phalloides are predicted to have the capacity to make more than 50 cyclic hexa-, hepta-, octa-, nona- and decapeptides.